2000
DOI: 10.1385/endo:13:3:369
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by Interleukin-6 and Inhibition by Tumor Necrosis Factor of Cortisol Release from Bovine Adrenal Zona Fasciculata Cells Through Their Receptors

Abstract: Interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha) are synthesized and released from adrenal cells. Therefore, the effects of TNF-alpha and IL-6 on cortisol release from bovine zona fasciculata (ZF) cells were investigated. IL-6 (10-1000 pg/mL) significantly increased basal and adrenocorticotropic hormone (ACTH)-stimulated cortisol release in a concentration-dependent manner. This stimulatory effect of IL-6 became apparent at intervals as short as 4 h and continued through 24 h. IL-6 also potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…IL6 receptors are present in the adrenal cortex of many species, including humans (3,(19)(20)(21). It has been shown that IL6 alone stimulates glucocorticoid release from primary cultures of rat, bovine and human adrenal cells (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL6 receptors are present in the adrenal cortex of many species, including humans (3,(19)(20)(21). It has been shown that IL6 alone stimulates glucocorticoid release from primary cultures of rat, bovine and human adrenal cells (19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IL6 alone stimulates glucocorticoid release from primary cultures of rat, bovine and human adrenal cells (19)(20)(21)(22)(23). However, in order to stimulate glucocorticoid release, a long incubation time (O12 h) is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding could indicate a better ACTH release with adrenal gland stimulation but not one sufficient to reach normal cortisol serum levels. Barney and colleagues found in bovine adrenal cells that TNF has an inhibitory effect on ACTH-stimulated cortisol released (23), therefore, we could be improving this balance in the adrenal cells. However, the anti-TNF-a therapy not only demonstrates TNF neutralization but also diminishes the interleukin(IL)-6 and IL-1 levels to some degree.…”
Section: Discussionmentioning
confidence: 95%
“…Some key mediators of increased serum levels of cortisol relative to DHEA, DHEAS or 17OH-progesterone may be (a) circulating cytokines such as TNF and IL-6, which exert their specific effects at the level of the adrenocortical cell (Jäättelä et al 1991, Päth et al 1996, Barney et al 2000, (b) local immune cells in the adrenal gland, which produce cytokines or act via surface molecules (Wolkersdorfer et al 1999), and (c) neurotransmitters or neuropeptides of innervating nerves of the adrenal glands, whose release may be under control of local cytokines (Ehrhart-Bornstein et al 1998). Since TNF can inhibit the secretion of cortisol from adrenal cells due to an inhibition of the P450c21 or other factors (Jäättelä et al 1991, Barney et al 2000, and IL-6 increases cortisol secretion (Päth et al 1996, Barney et al 2000, these cytokines may be relevant for early increased secretion of cortisol relative to DHEA, DHEAS or 17OH-progesterone during endotoxinaemia or chronic inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%